Oral History Program Interview: Hadley Leon Yocum - Yocum, Hadley Leon
CALIFORNIA STATE COLLEGE, BAKERSFIELD CALIFORNIA ODYSSEY The 1930s Migration to the Southern San Joaquin Valley Oral History Program Interview Between INTERVIEWEE: Hadley Leon Yocum PLACE OF BIRTH: Branch, Franklin County, Arkansas INTERVIEWER: Stacey Jagels